Comparable autoantibody serum levels against amyloid- and inflammation-associated proteins in Parkinson's disease patients and controls. - Walter Maetzler; Anja Apel; Markus Langkamp; Christian Deuschle; Sarah Selina Dilger; Johannes Georg Stirnkorb; Claudia Schulte; Erwin Schleicher; Thomas Gasser; Daniela Berg (PLoS ONE)
Naturally occurring autoantibodies (NAbs) against a number of potentially disease-associated cellular proteins, including Amyloid-beta1-42 (Abeta1-42), Alpha-synuclein (Asyn), myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG), and S100 calcium binding protein B (S100B) have been suggested to be associated with neurodegenerative disorders, in particular Alzheimer's (AD) and Parkinson's disease (PD). Whereas the (reduced) occurrence of specific NAbs in AD is widely accepted, previous literature examining the relation of these NAb titres between PD patients and controls, as well as comparing these levels with demographic and clinical parameters in PD patients have produced inconsistent findings. We therefore aimed, in a cross-sectional approach, to determine serum titres of the above NAbs in a cohort of 93 PD patients (31 of them demented) and 194 controls. Levels were correlated with demographic and clinical variables, cerebrospinal fluid Abeta1-42, total tau and phospho-tau levels, as well as with single nucleotide polymorphisms (SNPs) of genes which either have been reported to influence the immune system, the amyloid cascade or the occurrence of PD (ApoE, GSK3B, HLA-DRA, HSPA5, SNCA, and STK39). The investigated NAb titres were neither significantly associated with the occurrence of PD, nor with demographic and clinical parameters, neurodegenerative markers or genetic variables. These results argue against a major potential of blood-borne parameters of the adaptive immune system to serve as trait or state markers in PD.